The Association of Plasma Cell Density of the Microenvironment with Classical Hodgkin Lymphoma Stage - Neti, Neti; Murti, Krisna; Kartika, Ika (Majalah Patologi Indonesia, 2023)
Background Plasma cells are important prognostic factors in various malignancies including Classical Hodgkin lymphoma (CHL). In the CHL microenvironment, plasma cells are the main prognostic factors, but research of relationship between plasma cell density in the microenvironment and CHL stage is still very limited. This study aims to determine the relationship between plasma cell density in the microenvironment and the CHL stage. Methods A case series procedure was conducted. The samples were paraffin blocks of CHL patients at Anatomic Pathology Department of Faculty of Medicine Universitas Sriwijaya/Mohammad Hoesin General Hospital. Among 47 cases of CHL diagnosed from 1st Januari 2018 to 30th November 2022, only 30 cases were included. Immunohistochemistry was performed by using specific antibody of plasma cells (anti-CD138 antibody). The number of plasma cells in each sample was calculated based on the expression of CD138 in the cell membrane and cytoplasm with weak-strong intensity. Then the cut-off point value was determined based on the ROC curve to classify the high and low plasma cell densities. The density of plasma cells was correlated to clinicopathological characteristics including age, sex, tumor location, CHL subtypes and stage. Statistical analysis was performed using Spearman test of SPSS with significant consideration if p<0.05. Results A high proportion (>10,9) of tumour-associated plasma cells of the tumor microenvironment was found in CHL advanced stage. Spearman test resulted in a significant correlation between density of plasma cell with advanced stage classical Hodgkin lymphoma (p=0.000). Conclusions There is significant relationship between high density of plasma cells with CHL stage.